2018
DOI: 10.1089/neu.2017.5145
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Exposure to Repetitive Head Impacts Is Associated with Smaller Thalamic Volumes in Former Professional American Football Players

Abstract: Thalamic atrophy has been associated with exposure to repetitive head impacts (RHI) in professional fighters. The aim of this study is to investigate whether or not age at first exposure (AFE) to RHI is associated with thalamic volume in symptomatic former National Football League (NFL) players at risk for chronic traumatic encephalopathy (CTE). Eighty-six symptomatic former NFL players (mean age = 54.9 ± 7.9 years) were included. T1-weighted data were acquired on a 3T magnetic resonance imager, and thalamic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 74 publications
(94 reference statements)
0
64
3
1
Order By: Relevance
“…They divided participants into 2 groups based on AFE to tackle football (i. e., AFE < 12 years, AFE > 12 years) and reported that AFE < 12 years exhibited significantly worse performance on the Wisconsin Card Sorting Test, the Neuropsychological Assessment Battery List Learning and the Wide Range Achievement Test, 4th Edition [8]. This group followed up their initial work with subsequent studies, including neuroimaging and neuropsychiatric assessments, confirming that earlier AFE to tackle football may contribute to later-life neurological impairments in former NFL players [5][6][7][8][9]. In 2016, Solomon and colleagues failed to replicate the findings of Stamm and colleagues; in 45 retired NFL athletes, there were no associations between years of exposure to pre-high school football and neuroradiological, neurological, and neuropsychological outcome measures [35].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…They divided participants into 2 groups based on AFE to tackle football (i. e., AFE < 12 years, AFE > 12 years) and reported that AFE < 12 years exhibited significantly worse performance on the Wisconsin Card Sorting Test, the Neuropsychological Assessment Battery List Learning and the Wide Range Achievement Test, 4th Edition [8]. This group followed up their initial work with subsequent studies, including neuroimaging and neuropsychiatric assessments, confirming that earlier AFE to tackle football may contribute to later-life neurological impairments in former NFL players [5][6][7][8][9]. In 2016, Solomon and colleagues failed to replicate the findings of Stamm and colleagues; in 45 retired NFL athletes, there were no associations between years of exposure to pre-high school football and neuroradiological, neurological, and neuropsychological outcome measures [35].…”
Section: Discussionmentioning
confidence: 71%
“…Younger age of first exposure (AFE) to American football has been associated with later-life impairments in cognitive function, altered corpus callosum white matter microstructure, decreased thalamic volume, greater behavioral and mood symptoms and earlier age of neurobehavioral symptom onset in former National Football League and amateur players [5][6][7][8][9]. In current high school and collegiate American football players, younger AFE is not associated with deficits in behavioral, cognitive, psychological or physical performance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[115][116][117] Additionally, retired professional American football players show subcortical atrophy, including smaller thalamic volume, amygdala, and hippocampal volume, as well as cingulate gyrus volume. 118,119 Lower hippocampal and cingulate gyrus volumes correlated with lower cognitive performance 119 and thalamic volumes correlated with cumulative exposure and age at first exposure to head impacts in retired NFL players, 120 and with increased number of bouts in boxers. 121 Decreased cerebral metabolism as measured with FDG-PET was found in the cerebellum, pons, and medial temporal cortex in veterans exposed to blast injuries 122 ; in bilateral posterior cingulate cortex, parieto-occipital cortex, inferior frontal cortex, and cerebellum in boxers 123 ; in bilateral dorsolateral prefrontal cortices and right middle orbitofrontal cortex in retired boxers 124 ; and predominantly in the frontal and temporal lobes in retired American football players.…”
Section: Chronic Traumatic Encephalopathymentioning
confidence: 98%
“…When the VA-BU-CLF Brain Bank researchers diagnosed former NFL player Aaron Hernandez with CTE, it highlighted increasing observational research showing duration of play (rather than number of concussions) and age of first exposure are risk factors for CTE or related symptoms. 9,10,25,35,[46][47][48][49] According to McKee, who led the analysis, the 27-year-old suffered from stage III/IV CTE, the most severe case ever seen in someone younger than 40 years. 50 These findings gained experimental support when Dr. Lee Goldstein and colleagues published a new animal model of CTE in Brain in January 2018 that provided strong evidence that concussion symptoms were independent from CTE pathology.…”
Section: Promoting Policies For Protecting Youth Athletesmentioning
confidence: 99%
“…29 By decreasing the number of hits to the developing brain, and delaying the age of first exposure to tackle football, evidence is growing that athletes will reduce the risk of future cognitive and behavioral/mood challenges. 25,46,47 Soon after the launch of Flag Football Under 14, the Aspen Institute, an independent think tank, recommended youth football organizations like USA Football and Pop Warner shift to a standard of flag football under age 14 years. 52…”
Section: Promoting Policies For Protecting Youth Athletesmentioning
confidence: 99%